KONSELING ANAK SEBAGAI SARANA UNTUK MENUMBUHKAN KEGEMBIRAAN DAN KEPERCAYANA DIRI ANAK-ANAK PANTI ASUHAN PUTRA SANTA MARIA BORO, KULON PROGO, YOGYAKARTA - Faisal, Agus; Hendrysusanto, Antonius Glendnaldy; Rupang, Gregorius; Simanjuntak, Nora Dolisna; Kaunang, Vincentius; Aryanto, Antonius Galih Arga Wiwin (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Child counseling is an attempt to assist children individually for guiding and helping them directly so that they can open them up and develop to be a sound person psychologically, personally and spiritually. The personal approach is required so that children to be open and understand their life experiences in order that they may find joy and develop their confidence. In addition to personal approach, some works to foster their self-confidence and joy are carried out by doing their daily duties and responsibilities, developing talents and providing adequate spiritual support. This social service attempts to provide both personal and group assistance so that the orphanage children can grow optimally and can prepare their better future.